Primary hyperoxaluria complicated with liver cirrhosis: A case report. Issue 12 (3rd March 2015) - Kogiso, Tomomi; Tokushige, Katsutoshi; Hashimoto, Etsuko; Miyakata, Chiharu; Taniai, Makiko; Torii, Nobuyuki; Omori, Akiko; Kotera, Yoshihito; Egawa, Hiroto; Yamamoto, Masakazu; Nagata, Masao; Shiratori, Keiko
Abstract : Primary hyperoxaluria (PH) is a rare, autosomal recessive disorder characterized by overproduction of oxalate caused by a deficiency in a hepatic enzyme. The excess oxalate combines with calcium in the kidneys to form deposits of calcium oxalate, which can lead to nephrocalcinosis and renal failure. PH type 1 (PH1), the most common form of this disease, is caused by a deficiency of the liver‐specific enzyme alanine/glyoxylate aminotransferase (AGT). Liver transplantation is performed as a definitive therapy for PH to correct the enzyme defect. Usually, liver depositions are limited and liver function is normal without fibrosis. Here, we report an adult case of liver cirrhosis caused by PH1. A 28‐year‐old woman was admitted to our hospital under suspicion of PH1 and the presence of nephrocalcinosis. The patient had suffered from kidney stone recurrences from 17 years of age, and was initiated on hemodialysis due to renal failure at the age of 27 years. The serum level of oxalic acid was high, whereas the AGT level in the liver tissue was decreased. Thus, the patient was definitively diagnosed with PH1. Although she had normal liver function, surface nodularity and splenomegaly were detected by computed tomography, suggesting liver cirrhosis. The native liver showed micronodular cirrhosis and portal fibrosis. Several arterioles were filled with rhomboid and polyhedral refractile oxalate crystals and various portal tracts showed these crystals. Our case suggests that long‐term oxalosis can lead to liver cirrhosis; thus, PH should be considered one of the causes of liver cirrhosis.